Legal Implications of the Signing of a Power of Attorney Deed Imposing Mortgage Rights which are Not Done in the Presence of a Notary - Kholiq, Muhammad Idam (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
This research aims to review the implementation of a power of attorney to encumber mortgage rights (SKMHT) made before a Notary in a land office legal study and the legal consequences of a power of attorney to encumber mortgage rights (SKMHT) made before a Notary following the format of the national land agency, Research A power of attorney to impose mortgage rights (SKMHT) must be made in a notarial deed or PPAT deed, however in practice the notarial making of an SKMHT deed can only be carried out by following the SKMHT format of Perkaban Number 8 of 2012. A Notary when using the SKMHT form is subject to the procedures for filling out SKMHT blank and Notary Position Law (UUJN). Due to the discrepancy between the form of the Notarial deed as regulated in Article 38 UUJN and the format of the BPN, there are deficiencies which result in the SKMHT deed not meeting the criteria as an authentic Notarial deed. This research was analyzed descriptively analytically using a sociological juridical approach. By using a sociological juridical approach. A Notarial deed must fulfill formal and material requirements to be declared a Notarial deed which has the power of proof as an authentic deed. This research analysis uses the theory of legal certainty and legal protection. From the results of this research analysis, it turns out that the SKMHT format does not comply with the form of Notarial deed stipulated by UUJN. SKMHT made before a Notary is not in accordance with UUJN provisions, so all legal acts that occur after the SKMHT takes place will not maintain the quality of the deed, it will become a private deed, if the formal requirements of a Notarial deed are not fulfilled. If the Notary's deed causes losses, you can file a civil lawsuit and the Notary can be subject to civil sanctions and compensation costs and interest against the Notary concerned. Suggestions for Notaries in carrying out their positions must be in accordance with the provisions of applicable law. Therefore, as long as the provisions regarding the form and procedures for filling out the SKMHT form have not been changed, a Notary must fill in the SKMHT form by also looking at the provisions contained in the UUJN. In this case, a Notary can make changes (renvoi) in the SKMHT Blank both at the beginning of the deed and at the end or closing of the deed, so that the SKMHT deed made by the Notary still has perfect evidentiary power.